2013
DOI: 10.1371/journal.pone.0057165
|View full text |Cite
|
Sign up to set email alerts
|

Differential Intrahepatic Phospholipid Zonation in Simple Steatosis and Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) occurs frequently in a setting of obesity, dyslipidemia and insulin resistance, but the etiology of the disease, particularly the events favoring progression to nonalcoholic steatohepatitis (NASH) as opposed to simple steatosis (SS), are not fully understood. Based on known zonation patterns in protein, glucose and lipid metabolism, coupled with evidence that phosphatidylcholine may play a role in NASH pathogenesis, we hypothesized that phospholipid zonation exists in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 45 publications
4
64
0
Order By: Relevance
“…PC depletion has been implicated in the pathogenesis of NAFLD (17,18,43,44). The current studies demonstrate that alcohol consumption in the background of obesity can lead to depletion of PC.…”
Section: Obesity Increased Hepatic Ces and Dag Hepatic Cesupporting
confidence: 50%
“…PC depletion has been implicated in the pathogenesis of NAFLD (17,18,43,44). The current studies demonstrate that alcohol consumption in the background of obesity can lead to depletion of PC.…”
Section: Obesity Increased Hepatic Ces and Dag Hepatic Cesupporting
confidence: 50%
“…Phosphatidylcholine metabolism through PMET is diminished and pan-zonal. 19 Although NASH patients have elevated serum bile acids and decreased lysophosphatidylcholine, the relationship between NASH and zone-specific functions remains largely unknown. 20 Mantena et al 21 found dysregulated oxygen gradient and mitochondrial effects in a high-fat diet NAFLD disease model in the mouse from which he postulates NASH and NAFLD alters the sinusoidal oxygen gradient so that zone 1 hepatocytes consume more oxygen but puts zone 2 and zone 3 hepatocytes into severe hypoxia ....................................................................................................................... in KO mice.…”
Section: Metabolic Zonation Nafld and Hccmentioning
confidence: 99%
“…For example, MALDI-IMS has been used to visualize the heterogeneous distribution of PC species in mouse brains [34], and effects of traumatic brain injury on the differential localization of PCs in rat brains [35]. Furthermore, MALDI-IMS detected alterations in phospholipid zonation in human livers with steatosis or nonalcoholic steatohepatitis (NASH) [36], and MALDI-TOF was used to measure serum lipidomic profiles in patients with NASH [37]. The present study examines the utility of MALDI-IMS for distinguishing glycerophospholipid profiles in experimental steatohepatitis produced in Long Evans rats by chronic ethanol, NNK or ethanol+NNK exposures.…”
Section: Introductionmentioning
confidence: 99%